Quantum dot labelling of adenovirus allows for highly sensitive single cell flow and imaging cytometry - Herod, Morgan R.; Pineda, Robert G.; Mautner, Vivien; Onion, David (Wiley-VCH Verlag, 2015)
A quantum dot method for highly efficient labelling of single adenoviral particles is developed. The technique has no impact on viral fitness and allows the imaging and tracking of virus binding and internalisation events using a variety of techniques including imaging cytometry and confocal microscopy. The method is applied to characterise the tropism of different adenoviral vectors.